2003
DOI: 10.1046/j.1365-246x.2003.01982.x
|View full text |Cite
|
Sign up to set email alerts
|

Radar Doppler velocimetry of volcanic eruptions: theoretical considerations and quantitative documentation of changes in eruptive behaviour at Stromboli volcano, Italy

Abstract: SUMMARY The use of radar Doppler velocimetry for the observation of volcanic activity is new. We used this method to continuously observe the activity of one vent of Stromboli volcano, Italy, from the end of 2000 April until early May. During this period we recorded 702 eruptions, 132 of which occurred before a strong rain storm passed over the island on April 29. In order to interpret the recorded Doppler data we developed a program that simulates different strombolian eruption scenarios, for which we then ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
44
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 39 publications
5
44
0
Order By: Relevance
“…Using minute-by-minute records of rainfall and seismic activity, Matthews et al (2002) observed a volcano-seismic response just 2 hours after intense rainfall fell at the SHV during the dome collapse of 29 July 2001. Similarly, Hort et al (2003) noticed an increase in the longevity of explosions at Stromboli volcano as recorded by Doppler radar in the hours following a single rainfall event. Neuberg (2000) found a correlation between seismicity, rainfall and ambient temperature on Mt.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Using minute-by-minute records of rainfall and seismic activity, Matthews et al (2002) observed a volcano-seismic response just 2 hours after intense rainfall fell at the SHV during the dome collapse of 29 July 2001. Similarly, Hort et al (2003) noticed an increase in the longevity of explosions at Stromboli volcano as recorded by Doppler radar in the hours following a single rainfall event. Neuberg (2000) found a correlation between seismicity, rainfall and ambient temperature on Mt.…”
Section: Introductionmentioning
confidence: 76%
“…This includes the triggering of eruptive episodes at basaltic volcanoes (Violette et al, 2001) including Strombolian explosions (Hort et al, 2003), shallow explosions at more silicic dome-forming eruptions (Mastin, 1994;Yamasato et al, 1998;Elsworth et al, 2004;Barclay et al, 2006) and lava dome collapse, meaning here a sustained volcanic event involving many individual rockfalls and pyroclastic flows over a period of up to a few hours (Yamasoto et al, 1998;Herd et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A potential way to obtain such constraints is through careful measurements of paths and velocities of ejecta emitted from a volcanic vent. Tracking of pyroclastic particles by video analysis has been shown to be a tool that gives valuable insights into crater processes (e.g., Hort et al 2003) as well as on the pressure (e.g., Taddeucci et al 2012;Gaudin et al 2014) and energy balances (e.g., Maeno et al 2013) of explosive eruptions. To date, such studies have been based on the analysis of ballistic trajectories (e.g., Mastin 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, velocity determinations using sodar require the knowledge of sound velocity at the jet temperature and gas composition, which was not available. Two main types of dedicated portable radars have since been used with the primary goal of studying eruption near-source dynamics through their Doppler capability: commercial micro rain radars, that are continuous-wave frequency-modulated and working at 24 GHz (Seyfried & Hort, 1999;Hort et al, 2003Hort et al, , 2006) and the VOLDORAD system, an L-band pulsed volcano Doppler radar (e.g., Dubosclard et al, 1999Dubosclard et al, , 2004Donnadieu et al, 2005). Being set up at a chosen location and aiming directly at the emission source (instead of rotation scanning), these compact radar systems can advantageously sound the gas thrust region and provide source eruptive parameters like eruption velocities, but also capture short-lived weak explosive activity, not visible to satellites or weather radars.…”
Section: Compact Portable Doppler Radars For Near-source Measurementsmentioning
confidence: 99%
“…They have higher temporal (<1 s) and spatial resolutions (tens to hundreds of meters) and higher sensitivity. A comparison of some characteristics of weather radars and transportable volcano Doppler radars is presented in Table 1 Hort et al (2003) found an increase in eruption duration, much higher velocities and indirect evidence of mean particle size decrease after a rain storm. Gerst et al (2008) reconstructed the 4D velocity (directivity) of Strombolian eruptions at Erebus and Stromboli from 3 FM-CW radars.…”
Section: Compact Portable Doppler Radars For Near-source Measurementsmentioning
confidence: 99%